Public Witness of the Church. Inspiration of Benedict XVI - Łużyński, Wiesław (Verbum Vitae, 2023)
Benedict XVI is a prominent theologian and an insightful observer of social life. One of the topics to which he devotes a great deal of attention is the presence of Christianity and the Church in the public sphere. The title of this article refers to a speech made by the pope during the ad lamina visit of the bishops of the United States, in which he explicitly states that “the Church’s witness is of its nature public.”1 This article aims to answer the question: What role do the Church and Christianity play in the public sphere? This is a very topical issue that is worth exploring more thoroughly. Particularly inspiring here is the teaching of Benedict XVI, who presents the topic in an interesting and original way. The descriptive analytical method was used in the preparation of the text. The following detailed issues will be submitted in the presentation of the topic: characterization of the public sphere, the place of the Church in this sphere, and the inspiring character of Christianity in the culture of nations that remain in an invigorating dialogue with Christianity and the Church. This article intends to shed light on the inalienability of Christianity in the socio-political culture of the West.